Radiologic Evaluation and Diagnostic Considerations in Anterior Elbow Dislocation - Alrasheed, Abdullah Aedh; Alahmadi, Bushra Khalid; Alghamdi, Samar Abdulrhman; Alhejaili, Ahmed Salim; Alhejaili, Mohammad Salim; Almutairi, Yousef Dhikl; Aljehani, Bandar Saleh; Gasem, Rafa Hussain; Alzahrani, Khalid Yousef Ali; Alshahrani, Ali Abdullah; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Anterior elbow dislocation is a rare injury, accounting for a small minority of elbow dislocations, and is frequently associated with high‑energy trauma and complex structural damage. Its rarity contributes to diagnostic uncertainty and challenges in management, particularly when compared with more common posterior dislocation patterns. Aim: This article aims to provide a comprehensive review of the radiologic evaluation, diagnostic considerations, clinical features, and management strategies of anterior elbow dislocation, highlighting key principles that optimize patient outcomes. Methods: A narrative review approach was employed, synthesizing current evidence and clinical insights related to elbow anatomy, mechanisms of injury, epidemiology, diagnostic imaging, management options, rehabilitation protocols, and prognosis. Special attention was given to differentiating anterior elbow dislocation from other traumatic elbow conditions. Results: Anterior elbow dislocation typically results from a fall onto a flexed elbow with an anteriorly directed force and is commonly associated with fractures, ligamentous disruption, and neurovascular injury. Accurate diagnosis relies on meticulous clinical assessment and appropriate radiographic imaging, including standard elbow views and adjunct imaging when indicated. Early closed reduction remains the cornerstone of management in acute cases, followed by short‑term immobilization and early mobilization. Surgical intervention is reserved for unstable, chronic, or fracture‑associated dislocations. Delayed treatment and prolonged immobilization are strongly associated with stiffness and functional limitation. Conclusion: Timely recognition, prompt reduction, careful neurovascular assessment, and structured rehabilitation are critical for optimizing outcomes in anterior elbow dislocation. Multidisciplinary coordination enhances recovery and minimizes complications.